2002
DOI: 10.1046/j.1467-789x.2002.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer: another aspect of the insulin‐resistance syndrome?

Abstract: Insulin resistance and compensatory hyperinsulinaemia are thought to be the underlying factors in the metabolic or insulin-resistance syndrome and can be controlled by diet and exercise. Hyperinsulinaemia has been shown to have a direct effect on the live, suppressing the production of sex hormone-binding globulin (SHBG) and insulin-like growth factor-binding proteins 1 and 2 (IGFBP-1, -2) while stimulating the production of insulin-like growth factor 1 (IGF-1). These factors have been proposed to be important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 59 publications
2
71
0
3
Order By: Relevance
“…13,14 It has been demonstrated that insulin resistance and hyperinsulinemia suppress the production of IGF binding protein 1 (IGFBP-1) and IGFBP-2 in the liver while increasing the production of IGF-1. 13 It has been reported that IGF-1 contributes to the initiation and progression of prostate cancer through a number of mechanisms, including increased proliferation of both normal and neoplastic prostate cells and inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 It has been demonstrated that insulin resistance and hyperinsulinemia suppress the production of IGF binding protein 1 (IGFBP-1) and IGFBP-2 in the liver while increasing the production of IGF-1. 13 It has been reported that IGF-1 contributes to the initiation and progression of prostate cancer through a number of mechanisms, including increased proliferation of both normal and neoplastic prostate cells and inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Insulin has been suggested to be an important factor in both BPH and PCa and both have been suggested to be additional aspects of the metabolic syndrome. 10,11 Future prospective trials should address the effects of this lifestyle modification on BPH symptomatology and progression.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Recently it has been suggested that hyperinsulinemia may be involved in the development of BPH and that it is an aspect of the metabolic syndrome, along with other common health problems including PCa. 10,11 We previously reported that a low-fat, high-fiber diet and daily exercise intervention reduced serum insulin, slowed the growth of serum-stimulated, androgendependent LNCaP, PCa cells while inducing apoptosis in the LNCaP cells. 12,13 The purpose of the present study was to test the effects of the low-fat, high-fiber diet and exercise intervention on serum-stimulated growth of primary prostate epithelial cells in culture.…”
Section: Introductionmentioning
confidence: 99%
“…10 Abdominal obesity, especially visceral fat, is associated with increased hepatic glucose synthesis and reduced glucose metabolism, higher free fatty acids and lower levels of SHBG 44 as well as with changes in inflammation and oxidative stress, 45,46 all factors that may increase risk of prostate cancer through different pathways (hormone-related, DNA damage and immune suppression). 36,38,47 BMI and waist circumference, however, were not risk modifiers in our study.…”
Section: Discussionmentioning
confidence: 99%